Defining Characteristics of National BIM Adoption - Rostam, Dilan M.; Atrushi, Dawood S.; Masih, Dawa A. A.; Abdulqader, Diman N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Building information modeling (BIM) has become a transformative force in the Architecture, Engineering, and Construction industry, streamlining project coordination, reducing costs, and promoting sustainability. Governments worldwide are mandating BIM to enhance efficiency and digital transformation in public projects. However, a roadmap of national adoption requires clear regulations, standardized frameworks, and skilled professionals. This study critically examines policy frameworks, legal considerations, and workforce readiness, educational strategies, identifying key enablers and barriers to national BIM implementation. Utilising a qualitative methodology, the research reviews global BIM adoption models, educational strategies, and legal challenges that serve the BIM adoption in Kurdistan Region. Findings emphasize the importance of BIM maturity models, structured training programs, and data interoperability. Recommendations include developing national BIM standards, integrating digital permitting systems, and fostering public-private collaboration. The Kurdistan Region faces regulatory gaps that hinder BIM validation and industry-wide adoption. Addressing these challenges through the Kurdistan National BIM Standards, aligned with global benchmarks such as ISO 19650 and BSI PAS 1192, will drive digital transformation, enhance project efficiency, and position Kurdistan as a leader in digital construction.